A hierarchical bilayer architecture for complex tissue regeneration - Min Yu (KeAi Communications Co., Ltd., 2022)
Engineering a complete, physiologically functional, periodontal complex structure remains a great clinical challenge due to the highly hierarchical architecture of the periodontium and coordinated regulation of multiple growth factors required to induce stem cell multilineage differentiation. Using biomimetic self-assembly and microstamping techniques, we construct a hierarchical bilayer architecture consisting of intrafibrillarly mineralized collagen resembling bone and cementum, and unmineralized parallel-aligned fibrils mimicking periodontal ligament. The prepared biphasic scaffold possesses unique micro/nano structure, differential mechanical properties, and growth factor-rich microenvironment between the two phases, realizing a perfect simulation of natural periodontal hard/soft tissue interface. The interconnected porous hard compartment with a Young's modulus of 1409.00 ± 160.83 MPa could induce cross-arrangement and osteogenic differentiation of stem cells in vitro, whereas the micropatterned soft compartment with a Young's modulus of 42.62 ± 4.58 MPa containing abundant endogenous growth factors, could guide parallel arrangement and fibrogenic differentiation of stem cells in vitro. After implantation in critical-sized complete periodontal tissue defect, the biomimetic bilayer architecture potently reconstructs native periodontium with the insertion of periodontal ligament fibers into newly formed cementum and alveolar bone by recruiting host mesenchymal stem cells and activating the transforming growth factor beta 1/Smad3 signaling pathway. Taken together, integration of self-assembly and microstamping strategies could successfully fabricate a hierarchical bilayer architecture, which exhibits great potential for recruiting and regulating host stem cells to promote synergistic regeneration of hard/soft tissues.